Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi Pada PT. Perkebunan Nusantara IV (Persero) Medan - Henny Zurika Lubis; Shahara Rambe; Sulaiman Effendi (-)
This study aims to analyze what factors affect the performance of accounting information systems at PT. Nusantara IV Plantation (PERSERO) Medan. The research used in this study is a quantitative approach using a purposive sampling approach, namely the sampling technique based on data sources with certain considerations totaling 30 employees. The data collection technique used in this study is a questionnaire (questionnaire), the analytical technique used in this study is quantitative data analysis techniques, namely using the calculation of numbers then draw conclusions from the test, with multiple linear regression, classical assumptions, partial test (t), simultaneous (F), coefficient of determination (R2). Based on the test results, there is an influence between personal technical skills, training and education on the performance of accounting information systems at PT. Perkebunan Nusantara IV (Persero) Medan. Indicates that tcount is greater than ttable. From these results, it can be concluded that Ha is accepted, Ho is rejected. Perkebunan Nusantara IV (Persero) Medan.